Menembus Batas Sosial: Kehadiran Anak Berkebutuhan Khusus Dalam Aktivitas Ekonomi Masyarakat Makassar - Mildayanti; Dwiyanti; Agung Muliaman Anas (Movere Journal, 2026)
This study explores how the economic participation of children with special needs (CSN) creates transformative mechanisms within the social sphere of Makassar City. Using an interpretative phenomenological approach, I conducted in-depth interviews with 19 informants (7 CSN entrepreneurs, 5 family members, 4 business actors/consumers, and 3 institutional representatives) between March and July 2024. The IPA analysis identified four key themes: (1) the economic domain as an arena for negotiating social identity shifting the label from “pitiable disabled individuals” to “competent economic actors”; (2) sophisticated economic adaptation strategies that foster technical innovation and mobilize social capital; (3) repeated economic interactions that gradually transform public social perceptions, though often generating ambivalent attitudes; and (4) the reinterpretation of the cultural values of siri’ and pacce’ within economic activities, which play an ambivalent role in promoting social inclusion. The findings reveal that economic access not only enhances the financial independence of CSN but, more fundamentally, functions as a mechanism for social acceptance and recognition of their existence in public spaces. Nevertheless, the observed inclusion remains tokenistic—CSN are accepted within the economic space while their social positioning remains marginal. Intersectional analysis further uncovers compounded socio-economic barriers for female CSN (a double disadvantage), while younger generations benefit from the gradual shift in social norms. This study contributes by demonstrating that economic inclusion serves as an alternative pathway toward broader social inclusion, emphasizing the need for a paradigm shift from charity-based to rights-based economic participation to achieve genuine social acceptance.